Species specific marker peptides for meat authenticity assessment: A multispecies quantitative approach applied to Bolognese sauce. (March 2019) - Prandi, Barbara; Varani, Martina; Faccini, Andrea; Lambertini, Francesca; Suman, Michele; Leporati, Andrea; Tedeschi, Tullia; Sforza, Stefano
Abstract: Food frauds are a critical issue in the field of food safety and quality. Given the high added value, and the complexity of the matrix, processed meat products are among those most susceptible of adulteration. Despite all the efforts made by the official control authorities and by the food industry to counteract these frauds, the undeclared replacement of meat species with cheaper ones is still widespread. The meat species allowed for food consumption are many, and their specific and accurate detection in highly processed food products requires very sensitive and selective analytical methods. In this work, a LC-MS method was developed to identify and quantify eight different meat species (duck, rabbit, chicken, turkey, buffalo, equine, deer and sheep) in a complex food matrix, such as Bolognese sauce. After protein extraction and trypsin digestion, a species-specific peptide marker for each species was chosen for qualification and quantification. The method was validated on real Bolognese sauce samples prepared in an industrial environment, showing a good sensitivity (LOD 0.2–0.8% on whole finished product) and the possibility, using specifically defined calibration lines, to quantify the amount of meat present coming from different species. Highlights: Species-specific marker peptides were identified for eight meat species. A LC-MS based method was developed for the detection of the marker peptides. Bolognese sauces were prepared with increasing amount of each species. Using proper calibration curves the method can quantify the meat species present. A validation was performed analyzing blind Bolognese sauce samples.